Long‐term consequences of membership in trajectory groups of delinquent behavior in an urban sample: Violence, drug use, interpersonal, and neighborhood attributes. Issue 6 (27th June 2013) - Brook, Judith S.; Lee, Jung Yeon; Finch, Stephen J.; Brown, Elaine N.; Brook, David W.
Abstract Research on stability and change in delinquent behavior over time has important implications for both the individual and the criminal justice system. The present research looks at this issue by examining the associations between the trajectories of delinquent behavior in adolescence and adult functioning. Data for the present study are from a four‐wave longitudinal study of African American and Hispanic participants. Participants provided information at mean ages 14, 19, 24, and 29. We used growth mixture modeling to extract trajectory groups of delinquent behavior in adolescence and young adulthood. Regression analyses were conducted to examine whether memberships in the trajectory groups of delinquent behavior from mean age 14 to mean age 24 were associated with violence, substance abuse and dependence, partner discord, peer substance use, and residence in a high‐crime neighborhood at mean age 29 when compared with the reference trajectory group of participants with low or no delinquent behavior. Four trajectory groups of delinquent behavior were identified: the no/low, the decreasing, the moderate, and the high persistent trajectory groups. Memberships in the trajectory groups were significantly correlated with variations in adult functioning. Memberships in some trajectory groups of delinquent behavior are significant predictors of later violent behavior, substance abuse and dependence, partner discord, peer substance use, and residence in a high‐crime neighborhood. The findings reinforce the importance of investing in interventions to address different patterns of delinquent behavior. Findings are discussed in relation to previous investigations with non‐Hispanic White samples. Aggr. Behav. 39:440–452, 2013. © 2013 Wiley Periodicals, Inc.